2014
DOI: 10.1007/s00436-014-3840-x
|View full text |Cite
|
Sign up to set email alerts
|

Olfaction in Asian tiger mosquito Aedes albopictus: flight orientation response to certain saturated carboxylic acids in human skin emanations

Abstract: The flight orientation response of nonblood-fed and hungry Aedes albopictus females was studied in a Y-tube olfactometer at 10(-6) to 10(-2) g odor plumes of saturated carboxylic acids (C1-C20), in which C2-C18 were the main constituents of human skin emanations. Thirteen acids viz C1, C2, C3, C5, C6, C8 C9, C10, C12, C14, C16, C18, and C20 showed attractance at odor plumes ranging from 10(-5) to 10(-3) g doses, while five acids viz C4, C7, C11, C15, and C19 showed repellence at 10(-4) to 10(-2) g to test mosq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 28 publications
1
11
0
Order By: Relevance
“…Similar to our study, gravid females exhibited a dose-dependent reversal of response to bacterial cell density of a mix of 14 bacterial species with the percentage of females trapped on sticky screening increasing from 10 6 to 10 8 cells/mL and declining significantly at 10 8 cells/mL. Similarly, Seenivasagan et al [ 35 ] also demonstrated that carboxylic acids can act either as attractants or repellents, depending on their concentration.…”
Section: Discussionsupporting
confidence: 89%
“…Similar to our study, gravid females exhibited a dose-dependent reversal of response to bacterial cell density of a mix of 14 bacterial species with the percentage of females trapped on sticky screening increasing from 10 6 to 10 8 cells/mL and declining significantly at 10 8 cells/mL. Similarly, Seenivasagan et al [ 35 ] also demonstrated that carboxylic acids can act either as attractants or repellents, depending on their concentration.…”
Section: Discussionsupporting
confidence: 89%
“…After 20 washes, the mortality is strongly reduced whatever the type of ITN [ 19 – 24 ] indicating a reduction of the concentration of available insecticide on the net [ 36 ]. The attraction of washed ITNs might therefore indicate an insecticide dose-dependent reversal effect of orientation behavior as it has been observed for Anopheles gambiae with human-derived putative repellents [ 37 ] and for Aedes albopictus with several carboxylic acids [ 38 , 39 ]. Because ITNs are rarely washed 20 times in their lifetime [ 40 – 42 ], the kinetic of active ingredients on the fiber in relation with behavioral responses of mosquitoes are urgently needed to understand better the effect of consecutive washing on ITNs deterrence.…”
Section: Discussionmentioning
confidence: 99%
“…The number of adults found in each glass vial was recorded. The Preference Index (PI) and Percentage of Repellency (PR) were calculated using the formula of Seenivasagan et al (2014); (Aryani & Auamcharoen, 2016).…”
Section: Repellent Bioassaymentioning
confidence: 99%